ON THE RESOLVENT OF SOME CLASS OF GENERALIZED DIFFERENTIAL OPERATOR - A.V. BRATISHCHEV (Вестник Донского государственного технического университета, 2018)
In the article is given representation of the resolvent  for generalized differential operator  with generating function in the space of holomorphic functions.